Ant based Self-organized Routing Protocol for Wireless Sensor Networks - S.Kamilah and Rozeha A. Rashid, K.Saleem, N.Fisal, S.Hafizah, (International Journal of Communication Networks and Information Security (IJCNIS), 2009)
.